Description of Junior High School Students' Metacognition Abilities in Solving Mathematic Problems - Rizky Fadillah (Program Studi Pendidikan Matematika, 2023)
Metacognition is essential in learning, especially in mathematics because students will be aware of their thinking processes in making plans, monitoring, and evaluating problem-solving. The purpose of this study is to describe the metacognition of junior high school students when solving math problems. This is a qualitative study with a case study design. The study included 32 eighth-grade students as participants.Tests and semi-structured interviews were used to collect data in this study. The researcher is the primary instrument in this study, with additional instruments such as straight-line equation tests and interview guides. A purposive sampling technique was used to select three of the study's 32 subjects. The study showed that: 1) The metacognition ability of subjects with high math scores when solving straight-line equation problems can achieve all indicators at each stage of metacognition. 2) The metacognition ability of subjects with moderate math scores when solving straight-line equation problems cannot achieve all indicators in the evaluation stage. 3) The metacognition ability of subjects with low math scores when solving straight-line equation problems, not all indicators in the information management strategies and debugging strategies stages can be achieved. Then none of the indicators in the evaluation stage can be achieved.